Role of laparoscopic surgery in blunt abdominal trauma; retrospective analysis in a tertiary trauma center - Rifan Alyami; Ahad E. Alotaibi; Leen Almohayya; Ajyad Al Jawad; Raghad Almukhayzim; Abeer Alhoumedan; Rakan S. Aldusari (BMC Surgery)
Abstract Purpose Trauma is a significant health concern globally and is one of the leading causes of illness and death. The laparoscopic approach has gained popularity in trauma care since its inception, becoming increasingly favored for both diagnostic and therapeutic purposes. This study aims to reduce unnecessary laparotomies and assess the effectiveness of laparoscopy in managing patients with blunt abdominal trauma. Methods The study is a descriptive retrospective study using the medical records of patients with blunt abdominal trauma who were managed with laparoscopy in the Department of General Surgery, King Abdulaziz Medical City in Riyadh. The study period was from 2019 to 2023 and included patients > 18 years with abdominal blunt injury, hemodynamically stable patients, and responding to resuscitation. The relationship between laparoscopic procedures according to the patient’s demographic and characteristics was conducted using the Fischer Exact test and independent sample t-test. Values were considered significant with a p-value of less than 0.05. Results In this study, 74 patients were included, with 94.6% being males. The average age of the patients was 36.3 years (standard deviation of 12.5 years). The primary cause of trauma was motor vehicle accidents (MVAs), accounting for 91.9% of cases. The most common surgical approach used was laparotomy, performed in 71.6% of patients. Additionally, CT scans revealed that solid organ injuries were the most frequently detected type of injury, occurring in 41.9% of cases. Following surgery, 78.4% of the patients underwent therapeutic procedures after laparotomy, while 37.8% received therapeutic interventions post-laparoscopy. Conclusion While laparoscopic techniques have been used for decades in abdominal surgeries, a consensus on their effectiveness and accuracy in diagnosing blunt abdominal injuries in trauma settings is still lacking. Laparoscopy is considered safe and feasible for hemodynamically stable patients, and our findings suggest it is equally effective in trauma cases for those who can tolerate the procedure. We recommend conducting further studies with larger sample sizes and more variables to provide sufficient data to accurately assess the efficacy and safety of laparoscopy in trauma situations.